Vision-Based 3D-Reconstruction of Barley Plants - Elibol, Armagan; Posch, Stefan; Maurer, Andreas; Pillen, Klaus; Moeller, Birgit (SPRINGER-VERLAG BERLIN, 2013)
For multi-view 3D reconstruction robust standard procedures have been established and can directly be applied to many scenarios. However, the extraction of point correspondences as a prerequisite for reconstruction is demanding for various applications. Here we present a new analysis pipeline for 3D reconstruction in the field of barley plant monitoring. Barley plants show a significant structural and textural similarity rendering the application of standard procedures to extract correspondences impossible. Our new approach overcomes these problems by combining information from various cues over different stages. Experiments on real data prove the suitability of our approach to generate 3D models of the plants from which phenotypical data can easily be derived.
Keywords: 3D reconstruction; correspondences; multiple cues; barley; LEAF; SEGMENTATION; STEREO; IMAGES; Computer Science; Imaging Science & Photographic Technology